Laminated connections under tensile load at different temperatures and strain rates. (December 2017) - Santarsiero, Manuel; Louter, Christian; Nussbaumer, Alain
Abstract: In the last years, a novel typology of adhesive connections for structural glass application has emerged, known as laminated adhesive connections, which makes use of the transparent ionomer SentryGlas® (SG) from Kuraray and the Transparent Structural Silicon Adhesive (TSSA) from Dow Corning. Despite being used in several projects, limited information is available in literature on their mechanical behaviour and on the effects of strain rate and temperature. In this work the behaviour of laminated connections under tensile loading is studied by means of experimental, analytical and numerical analyses. The experimental investigations show that temperature and strain rate variations have important effects on the mechanical response of the connections. Two main interesting phenomena are also observed: the whitening phenomenon in TSSA and the development of bubble within the SG adhesive. The analytical studies of the stress state show that confinement state of the adhesive induces a non-uniform three-dimensional stress distribution in the adhesive with a dominant hydrostatic component of the stress tensor, which is observed to be in agreement with the experimental results. Three-dimensional finite numerical analyses show that the stress field deviates from the uniform distribution with a large gradient of hydrostatic and deviatoric stresses over the adhesive area. The output of the finite numerical model are then compared with the observations of the experimental campaigns. Herein, the full set of numerical results is synthetized by the definition of so-called stress factors. The latter allow to derive the three-dimensional stress state in the adhesive at different temperatures and to compute the stress peak in the non-linear stress field distribution. Finally, prediction models are proposed for the tensile resistance of TSSA and SG laminated connections. A logarithmic law is proposed for the strain rate effects for both TSSA and SG connections. Linear and inverse hyperbolic-tangent-based laws are instead proposed for the TSSA and SG temperature effects, respectively.